2020
DOI: 10.21203/rs.3.rs-72124/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sublingual Misoprostol Versus Manual Vacuum Aspiration for Treatment of Incomplete Abortion in Nigeria: A Randomized Control Study

Abstract: Objectives: To compare the effectiveness of single-dose sublingual misoprostol to manual vacuum aspiration in the treatment of incomplete spontaneous abortion in Enugu, Nigeria.Design: Multi-centre randomized controlled trialSetting: A teaching hospital, the University of Nigeria Teaching Hospital (UNTH) Ituku-Ozalla, Enugu and a private specialist hospital, Julius Memorial Specialist Hospital Enugu, Nigeria were used for the studyParticipants: In all, 212 consecutive consenting women with sonologically confi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Misoprostol is a promising medical treatment option as an alternative of MVA for its satisfactory rate of complete uterine evacuation, and tolerable adverse events. So far, several studies have been launched to appraise the feasibility of misoprostol as an alternative of MVA in conditions where medical equipment like ultrasonography or well-trained surgeons were not available, but the results of these studies varied from one another [13][14][15][16][17][18][19] . Consequently, we carried out this systematic review and meta-analysis to evaluate the relative e cacy, safety concerns and patients' subjective evaluation of misoprostol and MVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misoprostol is a promising medical treatment option as an alternative of MVA for its satisfactory rate of complete uterine evacuation, and tolerable adverse events. So far, several studies have been launched to appraise the feasibility of misoprostol as an alternative of MVA in conditions where medical equipment like ultrasonography or well-trained surgeons were not available, but the results of these studies varied from one another [13][14][15][16][17][18][19] . Consequently, we carried out this systematic review and meta-analysis to evaluate the relative e cacy, safety concerns and patients' subjective evaluation of misoprostol and MVA.…”
Section: Discussionmentioning
confidence: 99%
“…With a purpose to guide the choice between MVA and misoprostol in rst trimester incomplete abortion, several high-quality prospective randomized controlled trials have been carried out to weigh their e ciency for complete uterine evacuation as well as safety concerns, while inconsistency came up among studies [13][14][15][16][17][18][19] . Particularly, the prevalence of adverse events following MVA or misoprostol use in rst trimester incomplete abortion have varied greatly among different studies.…”
Section: Introductionmentioning
confidence: 99%
“…The convenience of medical method, reduction of occurrence of uterine syne chiae, absence of use of anaesthesia and the resultant compa rable outcomes with surgical methods made it an easier and convenient method of uterine evacuation recently. 36,37 The use of medical management also reduces drastically the need for specialized surgical skills and therefore encourages task shifting and task sharing, making it easy to use even in secondary 34 and primary health care facilities. 38 Overall, there were no significant differences in adverse obstetric and perinatal risk to the mother and baby, between the two groups studied.…”
Section: Discussionmentioning
confidence: 99%
“…One research on women undergoing a voluntary termination of pregnancy reported that discomfort with misoprostol by sublingual route was 58+2.2 and vaginal route was 46.6+2.8 intraoperatively, which is comparable to our findings. 17 In a recent study 18 it was revealed that 203 patients were enrolled meeting the requirements for enrollment and ready to properly follow the protocol explained. Analysis of the data showed that percentage of the patients with complete abortions on misoprostol was 86% versus 100% in control group (p <0.01).…”
Section: Discussionmentioning
confidence: 99%